Sorpsi Isotermi dan Daya Patah Pada Emping Jagung Pulut - Kaslam Kaslam; Salengke Salengke; Helmi A. Koto (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Corn production in Indonesia is quite high, namely 18,364,430 tons with a total harvest area of ​​4,131,676 ha and productivity of 41.18% (BPS, 2010). One type of corn that is potential and widely developed is pulut corn. This type of corn is very suitable in making corn chips because it has a high amylopectin content (> 80%). Pulut corn chips are produced by many small to medium scale industries as snack food products. The problem that then occurs is the handling of post-production, corn chips have a high ability of water absorption so that when fried, it does not bloom perfectly so that it is less tasty to consume. The aim of this research is to test the sorption isotherm equations of corn chips that provide the approximate balance of water content that is closest to the measured equilibrium water content. By using temperatures of 25°C, 30°C and 35°C with a combination of 40%, 60% and 80% RH, this study shows that the Henderson equation provides an estimate of the behavior of isotermic soring sorut corn chips that is at a temperature condition of 30°C closer to the results experiment and also at a temperature of 35˚C. Whereas the Chung & Pfost equation best describes the behavior of isothermic absorption at 25OC. In addition, this study also aims to determine the fragility (fracture) of pulut corn chips in various storage conditions. Research shows that the higher the RH environment, the higher the fracture value.